Estimation of Innovative Clusters Efficiency Based on Information Management and Basic Models of Data Envelopment Analysis - Dmitry Vladimirovich Rodnyansky; Ruslan Agarunovich Abramov; Mikhail Leonidovich Repin; Elena Anatolevna Nekrasova (International Journal of Supply Chain Management, 2019)
Clusters and information management play an increasingly important role in the innovative development of regions and operational management. With the help of such structural entities, socially significant issues are being addressed, infrastructure development of the territories is being carried out, the investment climate is improving and various innovative projects are being implemented, new products, services, technologies are being created, the level and quality of life of the population is being raised. In our research we analyzed 24 innovative clusters created in the Russian Federation with the participation of the Ministry of Economic Development. We used econometric and statistical research methods. We analyzed financial investments made by both private investors and the state in the formation and development of clusters. After that, we compared the output parameters with the input financing and, based on the data envelopment analysis method, calculated the relative efficiency of the innovation clusters. We have identified 3 cluster benchmarks and made recommendations for improving the management system of the other clusters.